2016
DOI: 10.1097/md.0000000000003192
|View full text |Cite
|
Sign up to set email alerts
|

Piezosurgery for the Lingual Split Technique in Lingual Positioned Impacted Mandibular Third Molar Removal

Abstract: The aim of this study was to evaluate the effect and safety of lingual split technique using piezosurgery for the extraction of lingual positioned impacted mandibular 3rd molars with the goal of proposing a more minimally invasive choice for this common surgery.Eighty-nine consecutive patients with 110 lingual positioned impacted mandibular 3rd molars requiring extraction were performed the lingual split technique using piezosurgery. One sagittal osteotomy line and 2 transverse osteotomy line were designed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
6
0
3
Order By: Relevance
“…Postoperative reactions, including swelling, pain, and trismus, were used to evaluate the degree of surgical trauma. [ 20 , 21 , 34 , 35 ] Some authors reported that measurements of postoperative reaction reflected the degree of surgical trauma after alveolar surgery [ 24 , 27 , 34 ] , which was similar to the present study. This study showed that the MMO was slightly lower in the traditional surgery group than in the improved surgery group at 2, 3, and 4 days post-surgery, and we deduced that the long surgery time of traditional surgery might result in jaw elevator muscle spasm and extended period of soft tissue retraction, which was in line with the study described by Menziletoglu et al [ 29 ] However, there were no significant differences in pain, swelling, and trismus between the improved and traditional surgery groups, which verified that the improved surgery did not increase surgical trauma.…”
Section: Discussionsupporting
confidence: 90%
“…Postoperative reactions, including swelling, pain, and trismus, were used to evaluate the degree of surgical trauma. [ 20 , 21 , 34 , 35 ] Some authors reported that measurements of postoperative reaction reflected the degree of surgical trauma after alveolar surgery [ 24 , 27 , 34 ] , which was similar to the present study. This study showed that the MMO was slightly lower in the traditional surgery group than in the improved surgery group at 2, 3, and 4 days post-surgery, and we deduced that the long surgery time of traditional surgery might result in jaw elevator muscle spasm and extended period of soft tissue retraction, which was in line with the study described by Menziletoglu et al [ 29 ] However, there were no significant differences in pain, swelling, and trismus between the improved and traditional surgery groups, which verified that the improved surgery did not increase surgical trauma.…”
Section: Discussionsupporting
confidence: 90%
“…The average operating time of all the extractions was adequate compared with the previous studies 18 , 19 , 26 , 27 . The post-operative reactions 28 (pain, limited mouth-opening, swelling) are mild and acceptable compared with other studies of mandibular third molar extractions 10 , 18 20 . In the three cases of temporary IAN injury, all of the teeth located deeply and contacted or penetrated to the canals, which may be the cause of nerve injury 29 .…”
Section: Discussionmentioning
confidence: 67%
“…Pain level was measured with Visual analog scale (VAS) method 18 , 19 . Mouth opening was measured as the inter-incisal distance at maximum mouth opening 10 , 19 . Swelling was measured with standard caliper from the lingual aspect of mandibular 1st molar crown to the tangent of the cheek skin 20 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a piezoelectric tip is highly advantageous in minimizing damage to soft tissues. In comparison, thermal trauma and accidental mechanical trauma such as soft tissue damage can occur with a high-speed drilling device ( Chang et al, 2015 , Ge et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%